Clinically Deployable Bioelectronic Sensing Platform for Ultrasensitive Detection of Transferrin in Serum Sample - Kaur H.; Chittineedi P.; Bellala R.S.; Bellala V.M.; Singh S.; Kumari R.; Chandra P.; Pandrangi S.L.; Singh S.P. (My University, 2025)
Varying levels of transferrin (Tf) have been associated with different disease conditions and are known to play a crucial role in various malignancies. Regular monitoring of the variations in Tf levels can be useful for managing related diseases, especially for the prognosis of certain cancers. We fabricated an immunosensor based on graphene oxide (GO) nanosheets to indirectly detect Tf levels in cancer patients. The GO nanosheets were deposited onto an indium tin oxide (ITO)-coated glass substrate and annealed at 120 °C to obtain reduced GO (rGO) films, followed by the immobilization of an antibody, anti-Tf. The materials and sensor probe used were systematically characterized by UV–Visible spectroscopy (UV–Vis), X-ray diffraction (XRD), atomic force microscopy (AFM), and Fourier transform infrared spectroscopy (FTIR). Cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and differential pulse voltammetry (DPV) were also used for the stepwise sensor probe characterizations and Tf detection in serum samples, respectively. The anti-Tf/rGO/ITO immunosensor DPV output demonstrated an excellent Tf detection capability in the linear range of 0.1 mg mL−1 to 12 mg mL−1 compared to the enzyme-linked immunosorbent assay (ELISA) detection range, with a limit of detection (LOD) of 0.010 ± 0.007 mg mL−1. Furthermore, the results of the fabricated immunosensor were compared with those of the ELISA and autobioanalyzer techniques, showing an outstanding match with < 5% error and demonstrating the immunosensor’s clinical potential. © 2023 by the authors.